Serum Matrix Metalloproteinase-3 as a Noninvasive Biomarker of Histological Synovitis for Diagnosis of Rheumatoid Arthritis - Jian-Da Ma; Jing-Jing Zhou; Dong-Hui Zheng; Le-Feng Chen; Ying-Qian Mo; Xiu-ning Wei; Li-Juan Yang; Lie Dai (Mediators of Inflammation)
Objective. To explore the correlation between matrix metalloproteinase- (MMP-) 3 and histological synovitis in rheumatoid arthritis (RA). Methods. Serum MMP-3 of 62 patients with active RA was detected by ELISA. Serial synovial tissue sections from all RA patients, 13 osteoarthritis, and 10 orthopedic arthropathies patients were stained with hematoxylin and eosin and immunohistochemically for MMP-3, CD3, CD20, CD38, CD68, and CD15. Results. The percentage of lining MMP3+ cells was significantly higher in RA patients especially with high grade synovitis and it was significantly correlated with Krenn’s synovitis score r=0.574, P<0.001 and sublining inflammatory cells. Multivariate stepwise linear regression analysis revealed that the association of the percentage of lining MMP3+ cells with activation of synovial stroma, sublining CD68+ macrophages, and CD15+ neutrophils was stronger than other histological indicators. The percentage of lining MMP3+ cells was significantly correlated with serum MMP-3 in RA r=0.656, P<0.001. Serum MMP-3 was higher in RA patients with high grade synovitis than that of low grade synovitis and significantly correlated with synovitis score and activation of synovial stroma subscore (all P<0.05). Conclusion. Serum MMP-3 may be an alternative noninvasive biomarker of histological synovitis and RA diagnosis.